Descriptive study: knowledge construction of secondary science teacher during lesson study in SMP BPI 1 Bandung - D N Juita; S Hendayana; R Riandi (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Secondary science teacher may come from various science competencies’ background. Teacher with Physics, Biology, and Chemistry competencies’ background should teach science comprehensively. MGMP based lesson study is one of schools’ effort to help science teacher to discuss teaching material. The objective of this study is to investigate knowledge construction of secondary teacher on science content during lesson study. This descriptive study was designed with 3 cycles of lesson study which consist of 3 times of plan. Do and see for every single cycle. The participant comes from same school with various science competencies’ background teacher. Field note, video and its transcript are used to identify the characteristic of teachers’ knowledge construction. Verbal communication or critical dialogue among science teacher during plan and see phases are described to show classification of knowledge construction. Furthermore, dialogue between students and teacher during do phases are discussed to categorize type of class dialogue. The result of this study show that science teacher with different competencies’ background tend to re-construct their science knowledge while the other stand on cognitive imbalance.